Status Quo of Hybrid Coronary Revascularization for Multi-Vessel Coronary Artery Disease - Harskamp, Ralf E. (Ann Thorac Surg, 2013)
Hybrid coronary revascularization (HCR) combines bypass grafting of the left anterior descending (LAD) coronary artery with percutaneous coronary intervention (PCI) of non-LAD vessels. HCR has been performed as an alternative to CABG or multi-vessel PCI in thousands of patients since the late 1990s. In this review article, we provide an overview on patient selection, procedural sequence and timing, use of surgical techniques and anti- platelet agents. Additionally, patient recovery, satisfaction, costs and clinical outcomes of individual studies after HCR are evaluated. Future directions are also discussed, including the need for adequately powered randomized trials.